Enterprise Resource Planning (ERP) in Supply Chain Management (SCM) Operational Performance: A Systematic Literature Review - Kristanti, Pingki; Anshori, Mochammad; Andriani, Nurita (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Technological developments in the digital era have made competition in the business world increasingly fierce. Companies are competing to find ways to increase productivity to be able to produce products of better quality and in large quantities and quickly by utilizing technology. One of the many technologies that can be utilized in companies is Enterprise Resource Planning (ERP). Many companies have implemented this ERP system to support the company's operational performance and productivity. Company operations in creating products have different levels of difficulty. Every company has business management in carrying out these operational activities, namely Supply Chain Management (SCM). Starting from procurement of raw materials to distribution of finished products, many are managed by SCM. In order to make SCM performance more effective and efficient, technology is needed in its management. The technology that can be used is ERP. It is hoped that the implementation of this ERP can help SCM operational performance become even more productive.